Thermomechanical Manipulation of Electric Transport in MoTe2. (15th March 2021) - Kim, Dohyun; Lee, Jun‐Ho; Kang, Kyungrok; Won, Dongyeun; Kwon, Min; Cho, Suyeon; Son, Young‐Woo; Yang, Heejun
Abstract: Layered semimetals such as monoclinic MoTe2 and WTe2 demonstrate superconducting, topological insulating, and Weyl semimetallic states based on their unique electronic band topology. While doping concentration, lattice constants, and spin–orbit coupling can largely modulate the quantum states of the semimetals, a puzzling issue is that their functional carrier density and magnetoresistance for practical applications critically vary by temperature, which cannot be explained by the conventional phonon effect or a structural phase transition. Here, a native doping‐mediated thermomechanical manipulation of electric transport in semimetallic MoTe2 is reported, where effective transport is controlled by temperature in an equivalent manner to electric gating. Combining X‐ray diffraction, scanning tunneling microscopy, transport measurements, and first‐principles calculations, a Fermi level shift and subsequent changes in electronic structures are revealed as the origins of the practical transport changes in MoTe2 . Moreover, the initial doping state of the MoTe2, determined by the Te vacancy density in two different growth methods, reciprocally affects the thermomechanical lattice and band structure changes, which is promising for novel electronic applications such as magnetic sensors and memory devices with layered semimetals. Abstract : A native doping‐mediated thermomechanical manipulation of electric transport in semimetallic MoTe2, where effective transport is controlled by temperature in an equivalent manner to electric gating, is reported. The initial doping state of the MoTe2 affects the thermomechanical lattice and band structure changes, which is promising for novel electronic applications such as magnetic sensors and memory devices with layered semimetals.